Developing Mobile Learning Application as Instructional Media for Reading Comprehension - Wardatul Jannah; Shofi, Ahmad Thoyyib (Al-Lisan: Jurnal Bahasa, 2022)
Students nowadays are no longer enjoy reading printed books. They mostly read from their mobile phone or computers' screens. Teachers need to encourage students to read and comprehend texts. Teachers should adopt and adapt technology in teaching reading comprehension to students in light of the rapidly changing existence of technology. The purpose of this research is to develop appropriate media for learning reading. This research has employed Research and Development design based on ADDIE model. This model is used for media development by requiring 5 stages, namely: 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. The research subjects are the tenth graders and the English teacher. Both the media and language experts validated the developed product. The instruments used in the needs analysis are questionnaires for the students and interviews with the English teacher. The final result is in the form of a mobile application that suits the needs of teachers and students. This media consists of 63 slides. The size of this mobile application is 52 Mb. The developed application consists of three main menus and eleven sub-menus. They are the intro page, loading section, menu page, materials page, core competence page, vocabulary building page, learning summary page, exercise page, glossary page, verb form page, user’s guide page, lesson plan page, description of the product page, and exit page. The result of this research could be seen in the enthusiasm, development, and students’ interest in mobile application media. Therefore, it is recommended for teachers to use mobile applications in teaching reading and for other developers to develop applications for the learning process.